Heptaplex-direct PCR assay for simultaneous detection of foodborne pathogens. (December 2017) - Hasap, L.; Thanakiatkrai, P.; Linacre, A.; Kitpipit, T.
Abstract: Foodborne pathogens pose significant problems for public health and economy. The gold standard, cultivation, is time-consuming and costly. In this study, a heptaplex-direct PCR assay for simultaneous detection of seven foodborne pathogens without DNA extraction and enrichment was developed and validated. Seven virulent genes of target strains were amplified and found that the assay provided the expected PCR fragment of 583, 490, 415, 343, 224, 209, and 105 bp for Shigella spp., Shiga toxin-producing Escherichia coli (STEC), Streptococcus pyogenes, Campylobacter jejuni, Salmonella Typhi, Listeria monocytogenes, and Staphylococcus aureus, respectively. Validation study showed that the assay was highly reproducible, specific and sensitive (10 6 –10 0 CFU/ml of detection limit). Moreover, assay application on 22 artificially-contaminated and 100 food samples provided a statistically equivalent efficiency to the culture method. A heptaplex-direct PCR assay thus can be used in microbial forensic science.